2021
DOI: 10.3390/rs13091666
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Smallholder Maize Farms Using Multi-Temporal Sentinel-1 Data in Support of the Sustainable Development Goals

Abstract: Reducing food insecurity in developing countries is one of the crucial targets of the Sustainable Development Goals (SDGs). Smallholder farmers play a crucial role in combating food insecurity. However, local planning agencies and governments do not have adequate spatial information on smallholder farmers, and this affects the monitoring of the SDGs. This study utilized Sentinel-1 multi-temporal data to develop a framework for mapping smallholder maize farms and to estimate maize production area as a parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 65 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Another among those issues was often lacking adequate remote sensing information during agricultural control because of meteorological circumstances like fog. There have been numerous efforts that overcome issues, including an a technique described by Mashaba-Munghemezulu et al (2021), which substituted the absence of available material with knowledge of a combination of greater temporal data and poor remote sensing pictures. Two primary challenges which prohibit policymaking from using remote sensing information to track plants and predict agricultural output are environmental circumstances and inadequate chronological precision (Nguyen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Another among those issues was often lacking adequate remote sensing information during agricultural control because of meteorological circumstances like fog. There have been numerous efforts that overcome issues, including an a technique described by Mashaba-Munghemezulu et al (2021), which substituted the absence of available material with knowledge of a combination of greater temporal data and poor remote sensing pictures. Two primary challenges which prohibit policymaking from using remote sensing information to track plants and predict agricultural output are environmental circumstances and inadequate chronological precision (Nguyen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We found two articles that emphasized the importance of engaging small farmers in food production and fighting hunger, thus being able to collaborate in SDGs, but not with emphasis on vertical farms (Mashaba-Munghemezulu, et al, 2021, Vamuloh, et al 2019.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we also identified that land cover from Sentinel-1 and Sentinel-2 was also used in several works. Mainly, Sentinel-1 helped report indicator 6.6.1 [43], and it was also related to SDG 2 [57]. Meanwhile, Sentinel-2 was used to report indicators 15.1.1 and 15.1.2 [52], 11.1.1 and 11.3.1 [58], as well as new definitions for indicators 11.1.1, 11.2.1, 11.3.1, and 11.6.2 [59].…”
Section: Land: Biospherementioning
confidence: 99%